1980
DOI: 10.1002/jbm.820140607
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of residual glutaraldehyde in glutaraldehyde‐tanned collagen biomaterials

Abstract: Glutaraldehyde is commonly used to control physical and biological properties of collagen structure by means of intramolecular and/or intermolecular crosslinking of collagen molecules. Solubility, antigenicity, and biodegradation of naturally occurring or reconstituted collagenous matrices are effectively reduced by glutaraldehyde treatment. Adverse biological reactions to glutaraldehyde have been limited to infrequent contact dermatitis and to biocidal effects which are exploited in chemical sterilization med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
233
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(240 citation statements)
references
References 19 publications
6
233
0
1
Order By: Relevance
“…These results indicated that FBSA-H had better cytocompatibility with no inherent cytotoxicity. The slight cytotoxicity of FBSA-GA was in agreement with that described in Speer et al 26 We also found an individual cell passing through the petal of FBSA ( Figure 6A, indicated by arrow). All of this suggested that FBSA might be a good scaffold for threedimensional cell culture, especially for tumor cells.…”
supporting
confidence: 92%
“…These results indicated that FBSA-H had better cytocompatibility with no inherent cytotoxicity. The slight cytotoxicity of FBSA-GA was in agreement with that described in Speer et al 26 We also found an individual cell passing through the petal of FBSA ( Figure 6A, indicated by arrow). All of this suggested that FBSA might be a good scaffold for threedimensional cell culture, especially for tumor cells.…”
supporting
confidence: 92%
“…20 However during in vivo transplantation, GTA can be toxic due to the degradation of polymer. 20,21 Hence biocompatible water soluble carbodiimide class cross linker EDC has also been tried, which is widely used for cross linking collagen in dermal tissue engineering. 22 EDC crosslink the amino groups of one polypeptide chain with the carboxylic groups of the adjacent polypeptide chain by forming the extra amide bond without its incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of crosslinkers have been used for increasing the mechanical properties of these gels, the majority of these agents are cytotoxic or may induce an immune response when constructs are implanted in vivo. [20][21][22] Non-enzymatic glycation, the crosslinking of proteins via reducing sugars, has been shown to change the mechanical properties of proteins both in vivo and in vitro, [23][24][25][26][27][28][29] and is a recognized method for in situ processing of cell-seeded tissue constructs. 23,30 This mechanism of crosslinking has been developed to process collagen gels both in their solid state and in solution.…”
mentioning
confidence: 99%